Evaluation of agricultural potential and conflicts of use of land in Lajeado Pessegueiro watershed, Santa Catarina State, Brazil - Machado, Ludmila Nascimento; Loss, Arcângelo; Bacic, Ivan Luiz Zilli; Dortzbach, Denilson; Lalane, Heloísa de Campos (Revista de Ciências Agroveterinárias, 2017)
The objective of this work proposed the use of the Methodology for Land Suitability Classification in Santa Catarina State (MCAUTSC) and the Evaluation System of Agricultural Land Suitability (SAAAT), to assess the agricultural land potential and subsequent identification of land use conflicts in the Lajeado Pessegueiro watershed, Guarujá do Sul, SC. For the preparation of the land use maps, polygon overlapping of the physiography and soil mapping were performed. The Land Use Conflict map resulted from the overlapping of the Land Evaluation map with the Land Use and Coverage map. Through MCAUTSC methodology, the predominant land evaluation classes were suitable to annual crops (2d and 2e), with 35.92% of the area and of pastures (3dpr and 3prp), with 45.21% of the area. For land use conflicts, there was a predominance of underutilization class (31.20%), followed by land use conflicts class (28.45%), use with restrictions (23.43%) and use without restrictions class (16.92%). For SAAAT, the predominant land evaluation classes were suitable to pasture (4p = 32.6%) and to annual crops (2 = 29.3%). For land use conflicts, there was a predominance of use without restriction (52.76%) and use conflicts class (23.61%), with the lowest proportion for land use without restriction (6.25%). In most of the watershed area, both methods indicate suitability for pastures, differing only in some areas where MCAUTSC indicates pasture and SAAAT indicates regular suitability for annual crops. Overall, the indications for the annual crops areas were also the same considering both methods. The main difference between the methods is that MCAUTSC better defines the limiting factors of the area, while the SAAAT demonstrates the management level based on the level of available technology.